The Impact of Financial Ratios on the Financial Health of Companies Listed on the Stock Exchange - Alyasari, Haitham Hadi Talib; Mahmoodabadi, Hamid; Nazemi , Amin; Setayesh, Mohammad Hossein; Namazi, Navid Reza (Journal of Ecohumanism, 2024)
Organizational stability, insolvency, financial hardship, and accounting data quality are all connected to a company's financial health. Examining the financial health of companies is important from various aspects, especially in light of globalization and the expansion of communications. There are multiple methods to assess the financial health of companies and predict financial bankruptcy, among which statistical techniques are prominent. This study investigates the financial ratios impacting the Logit model-based financial stability of businesses listed on stock exchanges. The members of the statistical sample include 152 businesses that are listed on the Tehran Stock Exchange since 2011 to 2021. To test the hypotheses, regression analysis and Logit and Probit models were employed using EViews software. The results indicated that profitability and agency costs have a significant impact on the financial health of companies. However, financial leverage, current ratio, cash holding level, and working capital to total assets did not significantly affect the financial health of the companies.